New concept of desiccant-enhanced heat pump. (15th January 2018) - Tu, Y.D.; Wang, R.Z.; Ge, T.S.
Highlights: The outlet air of a novel heat pump rightly satisfies the required supply air. The COP was 6.2 under summer condition and 5.9 under winter condition. The heat pump powered by a 265Wp PV model can handle 10 m 2 floor area in Shanghai. Abstract: Comfortable, efficient and affordable heating, ventilation and air conditioning (HVAC) systems in buildings are highly desirable to achieve zero energy building effort. Traditional vapor compression air-conditioners hold a lower COP (coefficient-of-performance) (typically 3.2–3.8) because it often operates at a lower evaporation temperature (5–7 °C) and a higher condensing temperature (50–55 °C) caused by cooling-based dehumidification that handles both sensible and latent load together. Room temperature and humidity independent control or desiccant systems have been proposed to overcome these challenges, however, the COP of current desiccant systems is quite small and additional heat sources are usually used. In this paper, a desiccant-enhanced direct expansion heat pump (DDX HP) based on water-sorbing heat exchangers was reported, with an ultrahigh COP value of more than 6 without sacrificing any comfort and compactness. The efficiency is double in comparison with today normal room air conditioners, which is a breath-taking and revolutionary progress in HVAC industry. This new approach opens up the possibility of designing a zero energy building with DDX HP powered by solar PV, and the simulation results show that one PV model (265Wp) can effectively handle about 10 m 2 cooling load in Shanghai in summer.